Concession Length and Investment Timing Flexibility - Michele Moretto; Chiara D. Alpaos; Cesare Dosi (Fondazione Eni Enrico Mattei (FEEM), 2005)
When assigning a concession contract, the regulator faces the issue of setting the concession length. Another key issue is whether or not the concessionare should be allowed to set the timing of new investments. In this paper we investigate the impact of concession length and investment timing flexibility on the concession value . It is generally argued that long-term contracts are privately valuable as they enable a concessionaire to increase her overall discounted returns. Moreover, the real option theory suggests that investment flexibility has an intrinsic value, as it allows concessionaires to avoid costly errors. By combining these two conventional wisdoms, one may argue that long- term contracts, which allow for investment timing flexibility, should always result in higher concession values. Our result suggests that this is not always the case. Firstly, investment flexibility does not always increase the concession value. Secondly, long-term contracts do not necessarily increase the concession value.
Keywords: D81; G31; L95; 330; Concession contracts; Real option theory; Investment timing flexibility; Water utilities